Long-term outcomes and prognostic markers in gallbladder cancer. Issue 28 (July 2018) - Cui, Xiwei; Zhu, Sha; Tao, Zhihang; Deng, Xinghao; Wang, Yexiao; Gao, Yuanjing; Liao, Yue; Ma, Weijun; Zhang, Yiwen; Ma, Xuelei
Abstract : Abstract: Cancer-related inflammation and systemic inflammatory markers have been widely recognized as an essential part in tumor multiplication, invasion, and metastasis of tumor cells. This study aimed to estimate and compare the prognostic value of various biomarkers on overall survival (OS) in patients with gallbladder cancer patients. We performed a retrospective study of 159 patients received different therapies in West China Hospital from 2009 to 2014. The preoperative biomarker data, including neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), monocyte–lymphocyte ratio (MLR), lactate dehydrogenase, and alkaline phosphatase, as well as other clinical information, were obtained from electronic record. And the receiver operating characteristic curves were used to analyze the optimal cut-off values of them. Kaplan–Meier survival analysis and Cox proportional hazard model analysis were applied to evaluate the association between markers and OS. The optimal cut-off value was 4.39 for NLR, 181.85 for PLR, 0.30 for MLR, and 3.02 for carcinoembryonic antigen (CEA). Kaplan–Meier analysis and univariate Cox analysis both demonstrated the significant prognostic value of NLR, MLR, and CEA. However, PLR failed to be a significant predictor of OS. The multivariate Cox analysis showed that preoperative NLR and CEA were independent prognostic factors for OS. Advanced tumor/node/metastasis stage, enhanced pretherapeutic NLR, and CEA were significantly associated with worse OS of gallbladder cancer patients. Furthermore, NLR was a better prognostic factor than CEA in advanced T (T3–T4) stage patients, while CEA was better for early T (T1–T2) stage, early N (N0–N1) stage, and early M (M0) stage patients.